Pharmacokinetics of Artemether-Lumefantrine and Artesunate-Amodiaquine in Children in Kampala, Uganda - Mwesigwa, Julia; Parikh, Sunil; McGee, Bryan; German, Polina; Drysdale, Troy; Kalyango, Joan N.; Clark, Tamara D.; Dorsey, Grant; Lindegardh, Niklas; Annerberg, Anna; Rosenthal, Philip J.; Kamya, Moses R.; et al. (Antimicrobial agents and chemotherapy, 2010)
The World Health Organization recommends the use of artemisinin-based combination therapies (ACTs) for the treatment of uncomplicated malaria. The two most widely adopted ACT regimens are artemether (AR)- lumefantrine (LR) (the combination is abbreviated AL) and amodiaquine (AQ)-artesunate (AS). Pharmacokinetic (PK) data informing the optimum dosing of these drug regimens is limited, especially in children. We evaluated PK parameters in Ugandan children aged 5 to 13 years with uncomplicated malaria treated with AL (n 20) or AQ-AS (n 21), with intensive venous sampling occurring at 0, 2, 4, 8, 24, and 120 h following administration of the last dose of 3-day regimens of AL (twice daily) or AQ-AS (once daily). AS achieved an estimated maximum concentration in plasma (Cmax) of 51 ng/ml and an area under the concentration-time curve from time zero to infinity (AUC0– ) of 113 ng h/ml; and its active metabolite, dihydroartemisinin (DHA), achieved a geometric mean Cmax of 473 ng/ml and an AUC0– of 1,404 ng h/ml. AR-DHA exhibited a Cmax of 34/119 ng/ml and an AUC0– of 168/382 ng h/ml, respectively. For LR, Cmax and AUC0– were 6,757 ng/ml and 210 g h/ml, respectively. For AQ and its active metabolite, desethylamodiaquine (DEAQ), the Cmaxs were 5.2 ng/ml and 235 ng/ml, respectively, and the AUC0– s were 39.3 ng h/ml and 148 g h/ml, respectively. Comparison of the findings of the present study to previously published data for adults suggests that the level of exposure to LR is lower in children than in adults and that the level of AQ-DEAQ exposure is similar in children and adults. For the artemisinin derivatives, differences between children and adults were variable and drug specific. The PK results generated for children must be considered to optimize the dosing strategies for these widely utilized ACT regimens.
Keywords: Pharmacokinetics; Artemether-Lumefantrine; Artesunate-Amodiaquine; Children; Uganda